Health Problems of Unorganised Urban MSME Workers of Nagaon, Assam: Assessing the health status and risks of unorganised urban MSME workers in Nagaon, Assam (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Workers in the unorganised MSM Enterprises are engaged in heterogeneous work activities which involve varied work related hazards and are consequent risk to health. The study aimed to explore the work-related health scenario in the urban enterprises of Nagaon district of Assam. One hundred thirty (130) workers from 14 different types of enterprises namely Welding Steel fabrication, Automobile servicing repairing, Tyre retreading, Printing binding, Engineering workshop, Soap manufacturing, Grinding Mill, Carpentry, Bakery, Electrical, Phenyl manufacturing, Dry betel nut factory, Perfumery oil extraction factory, Water hyacinth were assessed by interview using self-administered health questionnaire. There was a high prevalence of self-reported health problems among the workers in the selected enterprises. Study found that Lower Back Pain, Mental stress, Hypertension and high blood pressure, Musculoskeletal, Respiratory, Multiple Skin disease were most prevalent among the workers of the enterprises. Prevalence of different work injuries reported for highest Fracture and crash followed by Fallshitsslips injuries, Major Burns, Major cuts and Body part loss among the workers of the enterprises. Statistical significant relationships were found between different sets variables of physical, psychosocial, organisational factors and health effects aggravated to work ability loss, poor health condition and absence from work. The findings of the study suggest immediate attention with preventive intervention in these vulnerable groups of workers in the study area.